Identification and Pathogenicity of Causal Agents of Apple Canker Disease in Kazakhstan - Zhanar Tulegenova; Ulbike Amanbayeva; Aida M. Shalabayeva; Dina Yelyubayeva; Alikhan Zhaxylykov; Rabiga Uakhit; Ainura Smagulova; Vladimir Kiyan; Kazbek Dyussembayev; Gulzhamal Mukiyanova (Horticulturae)
Apples are widely consumed by people all over the world due to their taste and nutritional value. However, apple trees are prone to various environmental stresses, including fungal diseases. Among them, Cytospora canker (or Valsa canker) can cause dieback of branches and twigs. Although Kazakhstan is well known as an origin of apples, very little is known about canker diseases that spread across all commercial orchards. Therefore, an accurate identification of the causal agents of those diseases is needed for further application of informed disease management strategies. In this study, eleven isolates belonging to four Cytospora species were isolated from multiple cultivars, grown in six different orchards within the Almaty region, Kazakhstan. As a result of a multilocus phylogenetic analysis using ITS, LSU and tef1-α marker genes and morphological characterization, these isolates were described as Cytospora parasitica, Cytospora sorbina, Cytospora pruinopsis and Cytospora chrysosperma. Moreover, a pathogenicity test was conducted on detached twigs, and it demonstrated that two of these fungi were highly virulent. Overall, this paper is a first report of the causal agents of apple canker disease in Kazakhstan and could be a trigger for conducting future studies to better understand the disease epidemiology, as well as build management strategies.